The Influence of Transformational Leadership and Positional Promotion on Employee Performance with Work Motivation as an Intervening Variable: JEL Classification: M12, M54, D23, J24, O15 - Weti Yuliawati; Wibowo Wibowo; Franky Franky; Jubery Marwan (Newinera Publisher, 2025)
This study aims to examine the direct influence of transformational leadership, job promotions, and work motivation on employee performance, as well as the indirect influence of transformational leadership and job promotions, mediated by work motivation, in the Elementary School Directorate of the Ministry of Primary and Secondary Education. This is due to frequent leadership changes, with each leader having a different leadership style, which impacts employee performance. Lack of employee motivation is caused by employees feeling they rarely receive motivation during their work, which impacts employee performance. Lack of appreciation for employees impacts employee performance. Unclear career paths for job promotions impact employee performance. The research method used is an associative quantitative method with a correlational approach. The target population in this study was employees in the Elementary School Directorate of the Ministry of Primary and Secondary Education. The sample used in this study was all 61 employees in the Elementary School Directorate of the Ministry of Primary and Secondary Education. This study used linear regression analysis using SPSS software. The results showed that Transformational Leadership had a significant influence on Employee Performance. Job Promotion has a significant effect on Employee Performance, Work Motivation has a significant effect on Employee Performance, Transformational Leadership has a significant effect on Work Motivation, Job Promotion has a significant effect on Work Motivation, Work Motivation cannot mediate the effect of Transformational Leadership on employee performance, and Work Motivation cannot mediate the effect of Job Promotion on employee performance.